School exchanges between Germany and France: some new challenges and new opportunities as a result of the COVID-19 pandemic - Jourdy, Natalja (Glottodidactica, 2022)
The present paper examines the impact of the COVID 19-pandemic on school exchanges between Germany and France. Furthermore, it investigates teachers’ and students’ experiences with distance learning during this period. We highlight that the pandemic has generated many exceptional challenges, especially for vulnerable students. However, the pandemic-induced constraints have also stimulated the development of new didactic approaches, tools and methods. Therefore, we can speak about the new opportunities in the domain of education, and most precisely, for school exchanges.